2021
DOI: 10.1186/s12902-021-00791-w
|View full text |Cite
|
Sign up to set email alerts
|

The effect of comorbidities on glycemic control among Colombian adults with diabetes mellitus: a longitudinal approach with real-world data

Abstract: Background Achieving an optimal glycemic control has been described to reduce the incidence of diabetes mellitus (DM) related complications. The association between comorbidities and glycemic control remains unclear. Our aim is to evaluate the effect of comorbidities on glycemic control in people living with DM. Methods A retrospective longitudinal study on data from the National Registry of Chronic Kidney Disease from 2014 to 2019 in Colombia. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 40 publications
(55 reference statements)
0
13
0
Order By: Relevance
“…Patients who have one or more comorbidities have higher odds of having poor glycemic control, a result similar to what is reported in previous studies in Ethiopia ( 10 , 45 , 51 ). Similarly, a study conducted in Iran ( 52 ), Colombia ( 53 ), and North America ( 54 ) showed that type 2 diabetes mellitus patients who had comorbidities had a higher chance of poor glycemic control than those who didn’t have complications. The reason for respondents with comorbidities having poor glycemic control might be due to poor adherence to medication because of additional medication pill burden.…”
Section: Discussionmentioning
confidence: 99%
“…Patients who have one or more comorbidities have higher odds of having poor glycemic control, a result similar to what is reported in previous studies in Ethiopia ( 10 , 45 , 51 ). Similarly, a study conducted in Iran ( 52 ), Colombia ( 53 ), and North America ( 54 ) showed that type 2 diabetes mellitus patients who had comorbidities had a higher chance of poor glycemic control than those who didn’t have complications. The reason for respondents with comorbidities having poor glycemic control might be due to poor adherence to medication because of additional medication pill burden.…”
Section: Discussionmentioning
confidence: 99%
“…With a longer duration of diabetes, there is a deterioration of the function of the pancreas due to failure in beta cells, and the emergence of disease-related complications, which in turn can have effects on glycaemic control [8,111]. The presence of comorbidities/complications poses a problem with respect to pill burden, adherence to treatment and cost, or as an intricate mechanism linked to beta-cell impairment or aggravation of insulin resistance [8,94,[112][113][114][115][116][117]. In sub-Saharan Africa, there is a high proportion of undiagnosed diabetes mellitus, and the diagnosis is often delayed.…”
Section: Discussionmentioning
confidence: 99%
“…Another study stated that having diabetes and CKD or obesity increased the likelihood of developing poor glycemic control and elevated blood glucose level, in contrast to not having these concomitant conditions. Hypertension, however, was shown to have no connection with elevated blood glucose levels [ 22 ]. Similarly, a link between obesity and inadequate glycemic control was discovered in a cross-sectional study of the Iranian population with diabetes [ 23 ].…”
Section: Discussionmentioning
confidence: 99%